2015
DOI: 10.1103/physrevb.91.035437
|View full text |Cite
|
Sign up to set email alerts
|

Spin density wave and superconducting properties of nanoparticle organic conductor assemblies

Abstract: The magnetic susceptibilities of nanoparticle assemblies of two Bechgaard salts, (TMTSF)2PF6 and (TMTSF)2ClO4, have been studied vs. temperature and magnetic field. In the bulk these materials exhibit a spin density wave formation (TSDW = 12 K) and superconductivity (Tc = 1.2 K), respectively. We show from inductive (susceptibility) measurements that the nanoparticle assemblies exhibit ground state phase transitions similar to those of randomly oriented polycrystalline samples of the parent materials. Resistiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…With our results, we can hypothesize the contribution of the surface effects, where neutral BEDT-TTF molecules would be concentrated at the surface of the NPs or dispersed among NPs within the aggregates. This is in line with previous studies of (TMTSF) 2 ClO 4 NPs, where the superconductivity transition has been verified with an onset at about 1.2 K, the same transition temperature observed for single crystals [52]. XPS of the Se3d line of such (TMTSF) 2 ClO 4 NPs revealed several components, with a dominant Se 3d 5/2 feature at 55.7 eV, which corresponds to TMTSF in the neutral state, and less intense contributions at 56.1, 57.0, and 58.8 eV, respectively.…”
Section: Mixed Valency In Nanoparticles Of β-(Bedt-ttf) 2 Isupporting
confidence: 92%
“…With our results, we can hypothesize the contribution of the surface effects, where neutral BEDT-TTF molecules would be concentrated at the surface of the NPs or dispersed among NPs within the aggregates. This is in line with previous studies of (TMTSF) 2 ClO 4 NPs, where the superconductivity transition has been verified with an onset at about 1.2 K, the same transition temperature observed for single crystals [52]. XPS of the Se3d line of such (TMTSF) 2 ClO 4 NPs revealed several components, with a dominant Se 3d 5/2 feature at 55.7 eV, which corresponds to TMTSF in the neutral state, and less intense contributions at 56.1, 57.0, and 58.8 eV, respectively.…”
Section: Mixed Valency In Nanoparticles Of β-(Bedt-ttf) 2 Isupporting
confidence: 92%
“…The growth controlling agent evaluated in this study, namely an amphiphilic imine, prevented the preparation of (BETS) 2 FeCl 4 as micro-sized platelets or needles. This strategy, based on the use of a molecule bearing a heterocycle and a long alkyl chain and which has previously shown its efficiency for growing nanoobjects of TMTSF-and BEDT-TTF-based superconductors [8][9][10][11][12][13], was applied successfully here with BETS. We are currently exploring alternative experimental conditions to obtain nanoparticles of (BETS) 2 FeCl 4 with the λ-type structure.…”
Section: Discussionmentioning
confidence: 99%
“…The main families of growth controllers that we have explored were imidazolium-based ionic liquids, long alkyl chain quaternary ammonium salts, oligomers and neutral amphiphilic molecules [6,7]. Until now, we have successfully prepared nanoparticles of three ambient pressure organic superconductors, i.e., (TMTSF) 2 ClO 4 [8,9] (TMTSF: tetramethyltetraselenafulvalene), (BEDT-TTF) 2 I 3 [10,11] and (BEDT-TTF) 2 Cu(NCS) 2 [12,13]. In the present communication, we report on the preparation of the first nanoparticles based on the organic donor molecule BETS, i.e., bis(ethylenedithio)tetraselenafulvalene (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…We obtained stable dispersions of TTF[Ni(dmit) 2 ] 2 as well as other molecular conductors and superconductors, particularly Bechgaard salts[99] and (BEDT-TTF) 2 I 3[46]. The presence of superconductivity was demonstrated in (TMTSF) 2 ClO 4 nanoparticles[100].Charge injection from a metal electrode (generally Au) to an organic semiconductor (e.g., pentacene) is an important issue in the field of organic electronics[101]. It has been shown that replacing Au electrodes with molecular conductors such as TTF-TCNQ leads to lower contact resistance in bottom-contact transistors, which is explained by the morphological continuity between the electrode and the organic semiconductor, and by the absence of interfacial potential[102,103].…”
mentioning
confidence: 87%